Mexican local suppliers in home appliance value chains (2020)
This research aims to determine the factors influencing local supplier development by multinational subsidiaries in emerging countries like México. A quantitative regression methodology is employed using survey data collected from sourcing managers for a case-study focused on Mexico’s home appliance value chain. Although the extant literature suggests that a variety of factors influence local supplier development, only three factors were significant in this context: firm size, degree of autonomy, and technological capabilities. The applied research was conducted in the north of Mexico, where more than 50% of the domestic electrical products are produced; as such, the results generated herein could be reasonably representative of countrywide trends and phenomena. The context and results of this study could be useful to multinational companies in other emerging countries as they pursue development strategies vis-à-vis their local suppliers. Due to the scarcity of studies in México on value chains regarding local supplier development, the research presented here adds important knowledge on this topic. Keywords: Supplier Development, Value Chain, Household Appliances, Multinational companies, autonomy of the firm. JEL Code: F23, F63 Received: 29/05/2019. Accepted: 10/02/2020.  Published: 27/04/2020